The Role of Artificial Intelligence in Enterprise Resource Planning (Erp) Systems - Ozcan, Semiha; Akturk, Cemal; Cubukcu Cerasi, Ceren (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This study examines the role and impact of artificial intelligence (AI)-based methods in Enterprise Resource Planning (ERP) systems. ERP systems are critical tools that integrate all business processes to optimize data management. In this context, the integration of AI algorithms into ERP processes offers businesses new opportunities to accelerate decision-making mechanisms, enhance process efficiency, and optimize costs. The study elaborates on the contributions of AI in areas such as predictive analytics and process automation, presenting a strategic framework for businesses. The findings demonstrate that AI-supported ERP systems are powerful tools that increase businesses' ability to adapt to dynamic market conditions.